Methylation dependent expression of the mom gene of bacteriophage Mu: deletions downstream from the methylation sites affect expression. - Adley, C C (1984)
The expression of the DNA modification gene (mom) of bacteriophage Mu requires the cellular deoxyadenosine methylase (dam) and a transactivation factor from the phage. By hypothesis, the transcription of mom is activated by methylation of three GATC sequences upstream from the mom gene. We have introduced small deletions at a fourth GATC site located about 140 base pairs downstream from the primary methylation region. Some of the deletions severely affect the mom gene expression. We propose from this analysis that (1) some important elements, possibly the promoter, concerned with the expression of mom are located between nucleotides 840 and 880 from the right end of Mu and (2) the mom protein starts with the codon GTG located at position 810. We favor the hypothesis that methylation turns off transcription upstream, thereby allowing the main mom promoter to function.